APAKAH KEPERCAYAAN MEREK DAN KUALITAS PRODUK BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN? - Syam, Syaifullah; Launtu, Ansir; Themba, Orfyanni S. (Bussman Journal : Indonesian Journal of Business and Management, 2024)
Brands that consistently provide high quality products will more easily gain consumer trust, if consumers give confidence in a brand and the quality of a product then they will make the next purchase. This study aims to examine the effects of brand trust and product quality on purchasing decisions for jeans at Levi's Outlet in Makassar City. The population in this study were consumers who were found to be shopping for jeans at the Levi's Outlet Makassar Store in September - October 2024 which amounted to 82 respondents, with the sampling technique using by accidental sampling. Data analysis was carried out by multiple linear regression analysis with the help of SPSS 27 software. The results of this study provide evidence that brand trust and product quality have a significant positive effect on improving purchasing decisions. Product quality provides a more important effect than brand trust in improving purchasing decisions.